Studies on the role of inanimate surfaces and hands in the spread of hepatitis A virus and their chemical disinfection. - Mbithi, John J. Nzyoka. (University of Ottawa (Canada), 1993)
Hepatitis A (HAV) continues to be a serious problem for human health. The present study was designed to (a) assess the vehicular role of human hands and environmental surfaces in the spread of HAV; (b) evaluate the efficacy of chemical disinfectants and handwashing agents to eliminate HAV from inanimate and animate surfaces; and (c) determine the efficacy of alkaline glutaraldehyde reuse against HAV and other microorganisms. Pressure and friction were found to significantly affect HAV transfer between hands and inanimate surfaces (F = 33.98; p 0.05) irrespective of the mode of transfer used. No statistically significant interaction was observed between mode of transfer and pressure or friction. The findings of this phase of the study suggest that human hands and inanimate surfaces may play an important role in the direct as well as indirect spread of HAV. HAV disinfection was assessed on experimentally-contaminated metal disks. No virus was transferred from disks treated with a 3% solution of Virkon. None of the eleven handwashing agents examined, however, was able to reduce the infectivity titer of HAV and PV to an undetectable level. The least reduction in HAV titer was shown by an unmedicated soap (77.96 $\pm$ 7.17%), while the highest level of reduction was given by Bacti-Stat Medicated Soap (92.04 $\pm$ 4.02%). Samples of 2% alkaline glutaraldehyde were collected over the 14-day reuse period from two manual and one automatic bath used for the disinfection of flexible bronchoscopes and gastrointestinal endoscopes at a neighboring hospital. The number of instruments put through each bath during the 14-day cycle was recorded. The broad-spectrum germicidal activity of the disinfectant lasted only up to six days. This suggests a review of alkaline glutaraldehyde reuse in the disinfection of semi-critical instruments such as flexible fiberoptic endoscopes. These findings should help in understanding the genesis of HAV outbreaks more clearly and in designing better measures for their prevention and control. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.